Effect of extrusion technique on antinutritional factors of sorghum-soya blends - T V, ARUN KUMAR; MANI, INDRA; PRAMOD, A; SAMUEL, D V K; JHA, S K; SAHOO, P K; SINHA, J P; KAR, ABHIJIT (The Indian Journal of Agricultural Sciences, 2023)
Response surface methodology was used to assess the effect of soya level (10-30%), feed moisture content (12-20% w.b.), barrel temperature (110-150Â°C) and screw speed (250-450 rpm) on trypsin inhibitor activity (TIA),phytic acid (PA) and tannin content of the sorghum [Sorghum bicolor (L.) Moench]-soya blends. Results showed that incorporation of soybean [Glycine max (L.) Merr.] increased antinutritional factors in the feed formulation but extrusion cooking considerably reduced these factors in the extruded snack. The extent of reduction being up to 96% in TIA and 57% in PA and tannin content. Second-order polynomial model showed that soya level and barrel temperature significantly (P<0.01) influenced TIA, PA and tannin content whereas screw speed and feed moisture content showed influence only on TIA and PA, respectively. TIA, PA and tannin content of extrudates varied from1.456 to 6.658 TUI/mg, 177.53 to 311.83 mg/100g and 0.1942 to 0.4514% tannic acid, respectively. The results of the study validate extrusion as an effective technique for reducing of antinutritional factors to safe level for the production of sorghum-soya based extruded snack food.